2011
DOI: 10.1007/s10875-011-9630-7
|View full text |Cite
|
Sign up to set email alerts
|

Immune Reconstitution Following Unmanipulated HLA-Mismatched/Haploidentical Transplantation Compared with HLA-Identical Sibling Transplantation

Abstract: In this study, we prospectively investigated the immune reconstitution in patients with hematological malignancies after human leukocyte antigen (HLA)-mismatched/unmanipulated haploidentical transplantation (50 cases) and HLA-matched transplant (25 cases). Transplant-related mortality, relapse, leukemia-free survival, and overall survival were similar between the two transplant strategies, although the cumulative incidence of CMV antigenemia was significantly higher in haploidentical recipients than in HLA-mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
80
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(87 citation statements)
references
References 38 publications
7
80
0
Order By: Relevance
“…[16][17][18][19] Moreover, our previous study found that the T-cell subset and dendritic cell subgroup counts, especially CD8 + , CD4 + and CD4 + naive T cells, within the first 90 days post transplant were significantly lower in patients receiving haploidentical HSCT than in HLA-identical sibling HSCT (Po0.05). 20 As a result, the early delayed immune reconstitution after haploidentical HSCT probably led to an increased incidence of infection and infection-related mortality post transplant and finally led to a higher incidence of TRM. Therefore, the regular and intensive monitoring of pathogens after transplant was necessary for patients receiving haploidentical HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19] Moreover, our previous study found that the T-cell subset and dendritic cell subgroup counts, especially CD8 + , CD4 + and CD4 + naive T cells, within the first 90 days post transplant were significantly lower in patients receiving haploidentical HSCT than in HLA-identical sibling HSCT (Po0.05). 20 As a result, the early delayed immune reconstitution after haploidentical HSCT probably led to an increased incidence of infection and infection-related mortality post transplant and finally led to a higher incidence of TRM. Therefore, the regular and intensive monitoring of pathogens after transplant was necessary for patients receiving haploidentical HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…Soon after transplant, most CMV-CTLs are of donor origin, while newly "educated" endogenous T cells from thymic output appear only later [86]. In haploidentical HSCT, early T-cell recovery is primarily based on peripheral expansion of naïve T cells and it appears delayed when compared with that of HSCT from HLA-identical siblings [87][88][89][90] Long-term immune reconstitution, however, mostly thymus-dependent, appears appropriate to maintain an adequate naïve T cell pool [91][92][93][94]. Adoptively transferred CMV-CTL can be detected long after HSCT and up to 2 years after infusion [95].…”
Section: Adoptive T-cell Therapymentioning
confidence: 99%
“…Our results suggest that G-CSF and the pharmacological agent, ATG, are the two strategies that effectively control the alloreactivity resulting from HLA mismatching. Although a large number of T cells in the allograft presumably promotes immune recovery, 95 the incidence of acute and chronic GVHD was higher in patients receiving HBMT compared with those receiving TCD haploidentical transplantation. 16,17 These data suggest that the risk stratification-directed prophylaxis of GVHD (http://Clinical Trials.gov identifier NCT 01607580, 'Efficacy Study of Low-dose Glucocorticoid Prophylaxis for Acute Graft-versus-host Disease') should be explored as a method to decrease the incidence of acute GVHD following unmanipulated HBMT.…”
Section: Comparison Of the Underlying Mechanisms And Clinical Outcomementioning
confidence: 99%